Geographies of transition: The political and geographical factors of agrarian change in Tajikistan; Geographien der Transformation: Die politischen und geographischen Faktoren der Landreform in Tadschikistan - Irna Hofman; Oane Visser (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
After more than two decades of agrarian change in Tajikistan, farming structures seem to crystallise. The first signs towards farm individualisation were observed only around 2000, which were the result of significant pressure from outside, when the post-conflict state was highly susceptible to pressure from multilateral institutions. Over time, striking differences in agrarian structures have emerged nation-wide; from highly fragmented, autonomous farms, to elite-controlled large-scale cotton farming. In this paper we analyse and describe the Tajik path of reform, and locate the Tajik case amongst the other reformers in the CIS. We use a political economy and geographical approach to understand the way in which different geographies of transition have emerged in the aftermath of the Soviet collapse. Particular pathways of reform are conditioned by geographical factors, in which in turn, a local political economy comes into play that further shapes the emergence of particular farm models over time. – – Nach mehr als zwei Jahrzehnten der postsowjetischen Transformation in Tadschikistan scheinen sich (verschiedene) Strukturen in der Landwirtschaft heraus zu kristallisieren. Die ersten Anzeichen in Richtung einer Individualisierung waren erst im Jahr 2000 zu erkennen. Dies geschah vor allem aufgrund erheblichen Druckes von außen, als der Post-Konflikt-Staat anfällig war für den Druck von multilateralen Institutionen. Im Laufe der Zeit entstanden landesweit markante Unterschiede in den Agrarstrukturen. Diese reichen von stark fragmentierten, autonomen Betrieben, bis hin zu Eliten-gesteuerte Großbetrieben in der Baumwollproduktion. In diesem Beitrag analysieren und beschreiben wir den tadschikischen Weg der Reformen und vergleichen den tadschikischen Fall mit anderen postsowjetischen Ländern. Wir verwenden einen politisch-ökonomischen sowie einen geographischen Ansatz, um die Art und Weise von Landreform und Agrartransformation zu verstehen. Der Verlauf der Reformen ist bedingt durch geographische Faktoren. Hier entwickeln sich wiederum lokale politische Ökonomien, die weitere Formen von bestimmten Bauernbetrieben prägen.
urn:nbn:de:gbv:3:2-34506
Keywords: Q10; Q15; Z1; 330; agrarian change; political economy; former Soviet Union; Central Asia; Agrartransformation; politische Ökonomie; ehemalige Sowjetunion; Zentralasien